The Impact of Carbon Dioxide Emissions on the Economic Growth of India (International Journal of Innovative Research in Engineering & Management, 2022)
This study aimed to analyze the impact  of CO2 emissions on the economic growth of India. The  preliminary analysis of the data showed that CO2 emissions are on the rise in India. Further, the analysis  showed that carbon emissions are lower from the gaseous  fuel consumption than electricity and heat production,  and manufacturing industries, and construction. Similarly,  the carbon emissions from liquid fuel consumption are  lower than those from electricity and heat production but  higher than those from manufacturing and construction.  The analysis of the data proves that there is a connection  between these variables. Results of correlation analysis  and regression analysis showed that carbon emissions  have a negative and significant impact on India's  economic growth. Based on these results, we conclude that reducing carbon emissions is critical for the country's  well-being. As a result, the government should devise  strategies to reduce carbon emissions that are  environmentally benign. Environmental protection is a  long process requiring ongoing planning, government  regulations, and public and industrial participation.
Keywords: Economic growth; Carbon Dioxide Emissions; Carbon Intensity; Regression Analysis